The Blood Glucose Regulation in Intensive Care Unit (ICU) - Andriani, Ika Jati Setya; Jufan, Ahmad Yun (Jurnal Komplikasi Anestesi, 2022)
Glucose control among ICU patients has been a topic of debate over the past 20 years. Harmful effects posted by uncontrolled hyperglycemia and hypoglycemia among critically-ill patients have been acknowledged widely. Previous researches had proven that a tight glucose control is not only of no benefit, but instead harmful due to the increased risk of developing a significant hypoglycemia. Current guidelines suggest a moderate approach of intravenous insulin therapy initiation towards critically-ill patients with blood glucose level above 180 mg/dL. The most integral factor that underlies the glycemic management of patients in the ICU is the prevention of hypoglycemia. A robust glucose monitoring and insulin protocol strategies need to be implemented in achieving this goal. Keywords: glucose control, hyperglycemia and hypoglycemia, ICU